Structural Basis for Recognition of Cellular and Viral Ligands by NK Cell Receptors - Mariuzza, Roy; Li, Yili (Frontiers in Immunology, 2014)
Natural killer (NK) cells are key components of innate immune responses to tumors and viral infections. NK cell function is regulated by NK cell receptors that recognize both cellular and viral ligands, including MHC, MHC-like, and non-MHC molecules. These receptors include Ly49s, KIRs, LILRs, and NKG2A/CD94, which bind MHC class I molecules, and NKG2D, which binds MHC class I paralogs such as the stress-induced proteins MICA and ULBP. In addition, certain viruses have evolved MHC-like immunoevasins, such as UL18 and m157 from cytomegalovirus, that act as decoy ligands for NK receptors. A growing number of NK receptor–ligand interaction pairs involving non-MHC molecules has also been identified, including, NKp30–B7-H6, KLRG1–cadherin, and NKp80–AICL. Here we describe crystal structures determined to date of NK cell receptors bound to MHC, MHC-related, and non-MHC ligands. Collectively, these structures reveal the diverse solutions that NK receptors have developed to recognize these molecules, thereby enabling the regulation of NK cytolytic activity by both host and viral ligands.